Characterizing mechanical change in metals using amplitude-modulated diffuse ultrasound. (November 2020) - Xie, Fan; Zhang, Yuxiang; Larose, Eric; Duclos, Aroune; Chen, Su; Li, Xiaoyun; Fei, Chunlong
In this article, we present an ultrasonic method based on diffuse ultrasound with successive excitation amplitudes. This method provides amplitude-dependent parameters of diffuse ultrasound using coda wave interferometry, and these parameters can be used to characterize mechanical change in metallic materials. The localized mechanical change caused by an instantaneous 400°C thermal shock in a meter-scale aluminum alloy slab was characterized by measuring the diffuse-wave velocity change and decorrelation coefficient as functions of the excitation amplitude. The potential mechanisms and spatial distribution that cause the observed amplitude-dependent diffuse waveform modification are discussed. Combining the method presented here with complementary approaches will enhance the ability to nondestructively detect early-stage damage in the laboratory or in the field.